Terata catadidyma conjoined twins: how early you can diagnose - Todani, Ashok K.; Todani, Kiranlata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A conjoined twin is a complex process end-result considered to be caused by either delayed splitting of the fertilized ovum or fusion of the embryonic stem cells. Disorganization of mutant genes is believed to be a cause in some cases. Conjoined twins are described as having been physically fused during pregnancy and delivery. Division after 14th day of fertilization, results in an incomplete division, because once it becomes an embryo, it is incapable of fusion. The later the division, the more severe the effect. Conjoined twins were first mentioned a long time ago when there was not much known about this. They share some organs that are vital for survival, like the heart; these twins are almost impossible to save, but there are some cases wherein there is evidence of their survival. Current technology is providing a basis for earlier diagnosis and a better prognosis. MRI and CT scan provide excellent anatomic details later in pregnancy, demonstrating organ position, shared viscera, and vascular anatomy. We present a case of live Terata Catadidyma (which refers to twins joined in the lower portion of their body, or they may appear to be two bodies on top and one body on the bottom), diagnosed at 7 weeks and 3 days by non-invasive ultrasonography, hardly reported previously so early in the literature. This reported conjoined twin were having defect in occipital region of neurocranium (forming calvarium) which should have produced encephalocele later. So, early diagnosis inflicts much less physical and psychological trauma to parents concerning viability and pregnancy outcome in long run.